Safety Assessment of Genetically Modified Feed: Is There Any Difference From Food? - Giraldo, Paula A.; Shinozuka, Hiroshi; Spangenberg, German C.; Cogan, Noel O.I.; Smith, Kevin F. (Frontiers in Plant Science, 2019)
Food security is one of major concerns for the growing global population. Modern agricultural biotechnologies, such as genetic modification, are a possible solution through enabling an increase of production, more efficient use of natural resources, and reduced environmental impacts. However, new crop varieties with altered genetic materials may be subjected to safety assessments to fulfil the regulatory requirements, prior to marketing. The aim of the assessment is to evaluate the impact of products from the new crop variety on human, animal and the environmental health. Although, many studies on the risk assessment of genetically modified (GM) food have been published, little consideration to GM feedstuff has been given, despite that between 70 to 90% of all GM crops and their biomass are used as animal feed. In this article, the regulatory framework of GM crops intended for animal feed is reviewed and discussed. The first steps in such safety evaluation, molecular characterisation and traceability for GM feed are relatively established, since the same techniques can be used as GM food. However, environmental, nutritional, toxicological and allergenicity studies can vary depending on the trait nature and final consumer. A further development of specific methodologies for the assessment of GM crops intended for animal consumption is required, in order to provide a more accurate and standardised assessment to the GM feed safety.